OPTIMISING GROWTH AND YIELD OF TWO SESAME (Sesamum indicum L.) VARIETIES USING COW DUNG AND NPK 15:15:15 FERTILIZER IN JALINGO, TARABA STATE, NIGERIA - Boskina, Yusuf; Manager, Queen Idi; Ali, Jirah I.; Manga, Bakari A. (FUDMA JOURNAL OF SCIENCES, 2025)
Soil fertility remains a major constraint in sesame (Sesamum indicum L.) production, necessitating the use of organic and inorganic fertilizers to optimize growth and yield of sesame crop. This study evaluated the effects of cow dung and NPK 15:15:15 fertilizer on the growth and yield of two sesame cultivars at the Taraba State University Research Farm. A field experiment was conducted using a 2 × 4 factorial arrangement involving two sesame cultivars (local and improved) and four fertilizer treatments with three replications: cow dung (CD), NPK 15:15:15, a mixed application (50% CD + 50% NPK 15:15:15), and a control. Growth and yield data were collected and analysed using R statistical software (Version 20.5). Results showed that cow dung significantly enhanced plant height, leaf development, and yield components compared to other treatments. The highest plant height (83.96 cm) was recorded in the local variety treated with cow dung, while the lowest (65.13 cm) was observed in the local variety treated with LSVNPK alone. Cow dung-treated plants also produced the highest number of leaves (41.83), longest leaves (11.03 cm), and widest leaves (6.70 cm). Additionally, cow dung resulted in the highest number of pods per plant (9.13) and highest seed weight (35.3 g), compared to the control LSVC (13.40 g). No significant differences were observed between the two cultivars. The study concludes that cow dung is a highly effective organic fertilizer for improving sesame growth and yield, and its combination with NPK 15:15:15 further enhanced yield components.
Keywords: Sesame; Cow dung; NPK 15:15:15 fertilizer; Growth; Yield; Taraba State